2020
DOI: 10.1177/0003489420912446
|View full text |Cite
|
Sign up to set email alerts
|

Facial Paralysis and Communicative Participation: The Importance of Facial Symmetry at Rest

Abstract: Objective: There is a paucity of research devoted to understanding the communication restrictions encountered by facial paralysis patients. We aim to explore the relationship between patient-reported restrictions in communicative participation and objective facial paralysis severity using validated scales of facial movement. Methods: We performed a pilot retrospective study using a consecutive series of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Restrictions in communicative participation were captured by the CPIB for people with spinal cord injury (SCI), 86 facioscapulohumeral muscular dystrophy (FSHD), 87 and facial paralysis. 88,89 These studies revealed a range of communicative participation restrictions with, in some cases, the extent of the restrictions being commensurate with those resulting from more traditionally identified speech or language impairments. One finding of interest is that across these groups, conversational situations that require some element of speed or endurance such as having long conversations, getting your turn in fast-moving conversations, and having to say something quickly are situations that these participants found particularly challenging.…”
Section: Additional Populationsmentioning
confidence: 94%
“…Restrictions in communicative participation were captured by the CPIB for people with spinal cord injury (SCI), 86 facioscapulohumeral muscular dystrophy (FSHD), 87 and facial paralysis. 88,89 These studies revealed a range of communicative participation restrictions with, in some cases, the extent of the restrictions being commensurate with those resulting from more traditionally identified speech or language impairments. One finding of interest is that across these groups, conversational situations that require some element of speed or endurance such as having long conversations, getting your turn in fast-moving conversations, and having to say something quickly are situations that these participants found particularly challenging.…”
Section: Additional Populationsmentioning
confidence: 94%
“…Together, these deficits lead to significant functional and psychological impairment in emotional expressivity and communication, the sequelae of which significantly decreases the quality of patients' lives. [1][2][3] While most patients will ultimately see some degree of recovery over time, many experience persistent symptoms such as facial weakness, spasm, synkinesis, or aberrant tearing which can also negatively affect their daily living. 4 In an effort to quantify the patient experience, categorize severity, evaluate treatment outcomes, and monitor disease progression, a number of disease-specific outcome measures have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It manifests as facial asymmetry persisting for weeks to months, disappearance of forehead lines, inability to close eye clefts and frown, difficulties in drooping mouth, drooling, brushing teeth, gargling obstacles, eating, and chewing. [5][6][7] Some patients also experience ear pain and facial numbness. PFP is very common in clinical practice and predominately affects individuals aged 20 to 40 years with more males than females.…”
Section: Introductionmentioning
confidence: 99%